Inferential control of a flash separator for ethylbenzene production / Mohamad Najib Ismail - Ismail, Mohamad Najib (2018)
The research of the project is made based on a process control that implemented on a flash separator which is inferential control system. The control system is applied on a flash separator which run a chemical process of ethylbenzene production. Flash separator is an equipment that used in the process to separate between liquid and vapor. The objectives of this study are to find the dynamic relation between variables in a flash separator and to propose an inferential control system for a flash separator. The main focused of the research is to conduct a simulation study of the control system on flash separator. The purpose of using inferential control system is to determine the composition of a product out from a flash separator. The method used is not directly measured the composition, but by measure the secondary output to get the composition. It is because conventional method has some limitation on getting on-line reading of composition. The composition to be controlled in the process is ethylbenzene. Inferential control system is used to control the composition but by controlling other variables such as inlet temperature and pressure in tank. All the research were done by using simulation software for data collection and analysis. The software used were Aspen HYSYS and MATLAB-Simulink. This simulation software simulated the process to be most likely as the same parameter on real situation. For Aspen HYSYS, it used to get the dynamic relation between variables in the study and simulate the process with real condition while MATLAB-Simulink is used to simulate the control system with the behaviour of the process. Based on the result obtained, the inferential control system is a better alternative in order to solve real process control problem that always occur in process plant. The result shows that the inferential control system is able to control the composition of products bet set point tracking.